Taxonomic and molecular characterization of Pseudosteringophorus profundis sp. nov. (Digenea, Fellodistomidae), a parasite of Macrourus holotrachys Günther, 1878 (Gadiformes, Macrouridae) from the deep sea southeastern Pacific Ocean - Marcelo E. Oliva; Fabiola A. Sepúlveda; Rubén Escribano; Luis A. Ñacari (ZooKeys)
Pseudosteringophorus profundis sp. nov. a new species of deep-sea digenean, parasitizing the gallbladder of the “Bigeye grenadier” (Macrourus holotrachys Günther, 1878) in the deep waters of the southeastern Pacific Ocean is described on the basis of morphological and molecular (28S rRNA) data. The new species is distinguishable from Pseudosteringophorus hoplognathi Yamaguti, 1940, the only other member of the genus, by its subterminal oral sucker, the position of the ovary and testes, the larger anterior seminal vesicle compared to the posterior one, and its larger eggs. In addition, the new species is a parasite of a deep-sea fish, whereas P. hoplognathi is a parasite of shallow-water fish. A phylogenetic tree, based on 28S rDNA sequences, indicates that this species is included in a clade of deep-sea fellodistomid species (Steringophorus spp.). We provide the first molecular data on the genus Pseudosteringophorus Yamaguti, 1940 and expand the molecular database for the family Fellodistomidae. Further studies, including sequences from other fellodistomid taxa, are needed to more precisely infer relationships within this family.